Safe Handling of Antineoplastic Drugs in Oncology Nursing - Rujnan Tuna (Association of Nurse Managers, 2014)
Today the oncology nursing importance has been increased because of that cancer is one of the most important health problem in Turkey, as it is in the other countries throughout the world. By the way antineoplalastic drugs, which not only effect patients but also create negative effects on nurses, create negative working conditions for oncology nurses. The studies that compared nurses exposed to antineoplastic agents have been found the association between workplace explosure to antineoplastic and congenital malformations, ectopic pregnancies, miscarriages, stillbirths etc. In order to prevent all unwanted negative effects on effects, it has been necessary to develop standards and practice guidelines for preventive measures to be taken during the preperation and administration of antineoplastic drugs.